Governance Analysis Framework of Disabilities in Indonesia - Harits Hijrah Wicaksana; Muhammad Fauzi (Jurnal Manajemen Pelayanan Publik, 2024)
Fulfillment and protection of persons with disabilities has been realized with the approval of UN resolution A/RES/76/154. As a country that is a member of the UN, Indonesia adopted this resolution into Law No. 8/2016. So, how is the implementation and protection of people with disabilities in Indonesia? To answer this, this article uses a qualitative descriptive methodology with an ethnographic approach to qualitative analysis data processing using the Governance Analysis Framework method proposed by Hufty (2011). The research results reveal that the fulfillment and protection of people with disabilities in Indonesia is still not optimal. This is since the poverty rate for people with disabilities in Indonesia is still high, as can be seen from the low employment rate for people with disabilities. The low accessibility of education for people with disabilities makes it difficult for them to compete in the job market, resulting in low utilization of people with disabilities. Therefore, the orientation to protect oneself is decreasing due to low levels of welfare, so the role of government and organizations or institutions as well as groups of people with disabilities need to collaborate and synergize better.